Allogeneic Stem Cell Transplantation to cure Acute Myeloid Leukemia in elderly patients - Patel, Pritesh; Saraf, Santosh; Rondelli, Damiano (Journal of Advances in Internal Medicine, 2012)
Outcomes for elderly patients with acute myeloid leukemia (AML) remain poor with standard therapies. Historically this age group has been excluded from treatment with allogeneic stem cell transplantation (allo-SCT) due to worries of excessive treatment related morbidity and mortality. However, transplantation outcomes have dramatically improved in the last decade due to the widespread use of less ablative conditioning regimens, improved supportive care, and improved patient selection based on prognostic tools such as the hematopoietic cell transplant specific comorbidity index. These have all led to an increasing acceptance of allo-SCT as a potential treatment modality in elderly patients with AML. This review addresses current strategies for patient selection and efficacy data for allo-SCT in elderly patients with AML. DOI: http://dx.doi.org/10.3126/jaim.v1i1.5840 Journal of Advances in Internal Medicine. 2012; 1(1): 43-49